2020
DOI: 10.3389/frai.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Taxonomy for Adaptive Data Visualization in Analytics Applications

Abstract: Data analytics as a field is currently at a crucial point in its development, as a commoditization takes place in the context of increasing amounts of data, more user diversity, and automated analysis solutions, the latter potentially eliminating the need for expert analysts. A central hypothesis of the present paper is that data visualizations should be adapted to both the user and the context. This idea was initially addressed in Study 1, which demonstrated substantial interindividual variability among a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Tests revealed significant pairwise differences between the mean scores of PET's levels (see Figure 1 and Competent (M = 3.55 SD = .680), p < .05, based on their visual literacy; and (c) Expert (M = 4.42 SD = .496) and Competent (M = 3.94 SD = .617), p < .05, based on their self-efficacy (indicating the acceptance of (H 3 )). These results may imply on one hand that more expert users perceive also themselves as more knowledgeable and skillful in their line of business while on the other hand they may have the ability to understand and work with a wide variety of data visualizations for specific business tasks [29]. Furthermore, stakeholders that present higher levels of expertise and exercise also higher levels of self-efficacy characterized from high self-control and ability to moderate their behaviour to reach their goals.…”
Section: Analysis and Discussion Of The Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Tests revealed significant pairwise differences between the mean scores of PET's levels (see Figure 1 and Competent (M = 3.55 SD = .680), p < .05, based on their visual literacy; and (c) Expert (M = 4.42 SD = .496) and Competent (M = 3.94 SD = .617), p < .05, based on their self-efficacy (indicating the acceptance of (H 3 )). These results may imply on one hand that more expert users perceive also themselves as more knowledgeable and skillful in their line of business while on the other hand they may have the ability to understand and work with a wide variety of data visualizations for specific business tasks [29]. Furthermore, stakeholders that present higher levels of expertise and exercise also higher levels of self-efficacy characterized from high self-control and ability to moderate their behaviour to reach their goals.…”
Section: Analysis and Discussion Of The Resultsmentioning
confidence: 97%
“…There are many works that studied the influence of expertise (or experience) in the adaptation and personalization of data visualizations. Indicatively, [29] found that an initial understanding of the data visualization types could be predicted significantly by the business users' experience, in terms of education, working in a data-driven job, and the degree of statistical knowledge. Results which have been partially confirmed by [35], arguing that users' experience, besides preference, also affects satisfaction and the capability of being familiarized or switching between graphs to obtain information (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should use more data points with different numbers of trend reversals (i.e., slopes of adjacent lines from positive to negative or vice-versa), as it was shown that they have an impact on comprehension time (Carswell et al, 1993 ). Future studies should also examine how schema switches might affect graph processing when a single task involves comparisons between multiple (similar or different) graphs, that is, in complex graph display (e.g., see Riechelmann and Huestegge, 2018 ; Poetzsch et al, 2020 ). Other types of tasks should be used in future studies, such as a more basic “which is larger” comparison, A + B vs. C + D, as pie charts are ideal to combine even non-adjacent slices compared to summing up heights in bar graphs (Spence and Lewandowsky, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although significant effects have been observed in user-data visualization interactions by multiple works and in a variety of application domains, these ideas have rarely been applied, to our knowledge, to the business sector despite the encouraging findings [23]. Henceforth, the vision of this research work is to provide a preliminary step towards addressing this gap for enabling human-centred adaptive data visualizations that will facilitate efficient exploration and analysis of complex and multivariate business datasets, thus, enabling more effective decision making on critical business tasks.…”
Section: Introductionmentioning
confidence: 99%